Folk nomenclature and traditional knowledge of breadfruit [Artocarpus altilis (Parkinson) Fosberg] diversity in four Anglophone Caribbean countries - Oral O. Daley; Laura B. Roberts-Nkrumah; Angela T. Alleyne; Michael C. Gloster (BMC, 2022)
Abstract Background Since its introduction to the Anglophone Caribbean in 1793, breadfruit has had a diverse history in the region, and there is a considerable repository of traditional knowledge about the crop, that is undocumented. Consequently, it remains underutilized as a food source, despite recognition of its potential to contribute to food and nutrition security. Understanding the folk taxonomy and traditional knowledge associated with its diversity and uses is a prerequisite to develop programs for its commercial production and utilization. Method This study was conducted among 170 respondents who were selected across four Anglophone Caribbean countries and provided information on the ethnobotany and traditional knowledge associated with breadfruit biodiversity, including systems of naming, identification and classification of breadfruit cultivars or types. Results Breadfruit has socio-cultural and economic value and is produced for both home use and sale by most respondents (68%). The genetic diversity of breadfruit managed by the respondents is also important, as a total of 51 vernacular names were identified, with nine of those names recorded for the first time in this study. Breadfruit types were identified by morphological and agronomical characteristics, with other important traits relating to use and cooking quality. Classification of breadfruit cultivars or types was based on eating-quality, most suitable methods of preparation and ease of cooking. Conclusion The ethnobotanical and traditional knowledge obtained from this study may be useful in assessing the genetic diversity of breadfruit and guiding future community-based conservation and classification studies of this important crop resource in the Caribbean. This is crucial to support the commercialization of breadfruit to improve its contribution to food and nutrition security.